Public Support for Conducted Energy Weapons: evidence from the 2014 Alberta Survey - Oriola, Temitope B. (Canadian journal of criminology and criminal justice, 2016)
This paper examines support for the use of conducted energy weapons (CEWs) by police in Canada using data from the 2014 Alberta Survey (N = 1,204). Support for CEW use is measured using four Likert-scale questions, capturing different dimensions of CEW use: (1) “less-lethal” weapons such as Tasers should be made available to police officers; (2) Tasers are a safe policing tool; (3) the use of Tasers reduces levels of confidence in the police; and (4) official explanations regarding injuries and casualties in Taser-related incidents are satisfactory. Results of a logistic regression indicate that race, age, and gender are key predictors of perceptions of CEW use by police in Canada. Specifically, women, young people, and racialized minorities are least likely to be supportive of CEW use by police. Individuals identifying as white are over three times more likely to support CEW use by police, compared to those identifying as Aboriginal or members of another racialized group. Having a low household income, living in an urban area, and education are not statistically significant predictors of support for CEW use by police.